PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH KETERLIBATAN KERJA : KASUS PADA PT WANGSA JATRA LESTARI - Ahlul Prawira Yoga; Irmawati Irmawati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the influence of leadership and work environment on employee performance mediated by work engagement. The type of research used in this study uses quantitative methods. The population in this study is employees of PT. Wangsa Jatra Lestari. The sampling technique in this study is non-probability sampling. The calculation of the sample of this study is using Maholtra The number of samples of this study is 75 respondents. The data collection method used in this study is by distributing questionnaires. The data analysis technique in this study uses Partial Least Square (PLS) with the help of SMARTPLS Software. The results of the study show that leadership has a significant positive effect on employee performance. The work environment has a significant positive effect on employee performance. Leadership has a significant positive effect on work engagement. The work environment has a significant positive effect on work engagement. Leadership and work environment have a significant positive effect on employee performance mediated by work engagement